نموذج مقترح لقياس جودة الخدمة لدى أندية كرة القدم المحترفة في الجزائر - سعد, سعيدان (My University, 2018)
ملخص الدراسة: الدراسة بعنوان نموذج مقترح لقياس جودة الخدمة لدى أندية كرة القدم المحترفة في الجزائر،هدفت الدراسة إلى اقتراح نموذج لقياس جودة الخدمة بناء على مقياس الأداء ذو الأبعاد الخمسة وتعديله وفق البيئة الجزائرية وخصائص الخدمة لدى الأندية المحترفة، تمت الدراسة على عينة من 268 فرد من لاعبي ومدربي النوادي المحترفة لكرة القدم للرابطتين المحترفتين الأولى والثانية تشمل 11 نادي. ومن نتائج الدراسة أن النموذج المقترح يتكون من خمسة أبعاد رئيسية لجودة الخدمة هي التسهيلات، السلامة والاعتمادية، الجوانب المادية الملموسة، الجوانب المالية، وأخيرا الاستجابة والتعاطف، بينما الأبعاد الأصلية لمقياس الأداء هي الجوانب المادية الملموسة، الاستجابة، السلامة والأمان، ويمثل بعد التسهيلات أهم أبعاد جودة الخدمة في المقياس المقترح، وبعد الاستجابة والتعاطف أقل الأبعاد أهمية، عدد عبارات النموذج المقترح 40 عبارة، كما حافظ المقياس المعدل على عدد أبعاد الجودة لمقياس الأداء وهو خمسة أبعاد . Study Summary: The study is titled a proposed model for measuring the quality of service of professional football clubs in Algeria. The study aimed to propose a model for measuring quality of service Based on the five dimensional performance scale, And modify it according to the Algerian environment and the service characteristics of the professional clubs, A study was conducted on a sample of 268 professional players and coaches of the football clubs of the first and second specialized associations including 11 clubs. The results of the study suggest that the proposed model consists of five main dimensions of Quos: facilities, safety and reliability, tangible physical aspects, financial aspects, and finally response and empathy, While the original dimensions of the performance measure are tangible physical aspects, responsiveness, safety and security, and after the facility is the most important dimensions of service quality in the proposed scale, after the response and sympathy is less important dimensions, The number of expressions of the proposed model 40 words, and the modified scale also maintained the number of quality dimensions of the performance scale, which is five dimensions.
Keywords: اندية كرة القدم; المحترفة; قياس جودة الخدمة